Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae) - Kottelat, Maurice; Harries, Daniel R.; Proudlove, Graham S. (Zootaxa, 2007)
Schistura papulifera, new species, is described from a cave of the Synrang Pamiang system, Meghalaya State, India. It is distinguished from all other known species of Schistura in having the lower half of the head covered by small skin projections and 5 pores in the supratemporal canal of the cephalic lateral-line system. In addition, it has a white body and vestigial eyes. The closest epigean relative of S. papulifera has not yet been identified due to the lack of survey and usable data. The identity of the cave nemacheiline from Siju Cave is briefly discussed, but this remains inconclusive, again due to the lack of material and usable data.